PERLINDUNGAN HUKUM PEREMPUAN TERHADAP ANAK HASIL PERKAWINAN CAMPURAN DI INDONESIA (Perspektif Socio-Legal) - Rahmadi Indra Tektona (MUWAZAH : jurnal kajian gender, 2011)
Weak legal protection of women against children from mixed marriages, due to the patriarchal values are preserved through a process of socialization and reproduction in various forms by people and countries that are the order of the adam that marginalizes women. In other words, the law is built and constructed in a logical man. Therefore, to determine the status of the child and the relationship between children and parents, need to see first marriage of his parents as a preliminary issue, whether legitimate marriage of his parents so that children have a legal relationship with his father, or the marriage is invalid, so the child is considered as a child out of wedlock who only have a legal relationship with his mother. A child is legally considered a child born of a legitimate marriage between the father and mother.